Waterproof, breathable and moisture-permeable fabric and preparation method thereof

CN119261324BActive Publication Date: 2026-10-13SUZHOU GUANGKUN TEXTILE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411380671.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2026-10-13
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

此外,由于其是利用亲水无孔膜中大分子链进行湿气传导,因此在使用一段时间后不会因为刮擦或者洗涤而影响其透湿性,但是随着人们对功能性要求的提高,其透湿性渐渐不能满足人们的要求

Benefits of technology

[0024]1.本发明中采用具备疏水性的TPU层,面料层和排湿防水层复合而成,得到具有定向导湿的复合面料;将面料与TPU复合之前,先将面料浸泡于浓度比较低的壳聚糖溶液中,使面料的孔隙中渗透负载有壳聚糖,孔隙中渗透的壳聚糖充当毛细管的作用,而在面料浸泡低浓度的壳聚糖后在面料表面再涂覆一层湿壳聚糖凝胶,湿壳聚糖凝胶可以充当两个作用,首先,在壳聚糖是凝胶表面直接静电纺丝,静电纺丝膜和面料的复合不需要加粘合剂,壳聚糖静电纺丝膜可以很好的与壳聚糖湿凝胶粘附,其次,湿凝胶在干燥以后,其通过多孔结构,可以快速的将孔隙中吸附的水分蒸发出去,提高透气透湿的效果;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069821050000111
    Figure BDA0005069821050000111
  • Figure BDA0005069821050000121
    Figure BDA0005069821050000121
Patent Text Reader

Abstract

The application provides a waterproof, breathable and moisture-permeable fabric, which comprises a TPU layer, a fabric layer and a moisture-removing waterproof layer; the TPU layer is a TPU electrostatic spinning film; the moisture-removing waterproof layer is a chitosan electrostatic spinning film, and the chitosan electrostatic spinning film contains nano carbon spheres / hydrotalcite sheet materials; and the waterproof, breathable and moisture-permeable fabric is prepared from thermoplastic polyurethane and chitosan as raw materials, and then is combined with the fabric to obtain the fabric which is waterproof, breathable and moisture-permeable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional fabrics, specifically to a waterproof, breathable, and moisture-permeable fabric and its preparation method. Background Technology

[0002] Waterproof and breathable membranes are the core material of waterproof and breathable clothing. While resisting external elements like wind, frost, rain, and snow, they wick away sweat evaporated from the skin, maintaining a balanced microenvironment on the body surface and ensuring comfort. Due to their unique functions, waterproof and breathable membranes not only ensure comfort in harsh weather conditions but also meet the needs of both indoor and outdoor activities, and under certain conditions, they can also act as a barrier. Waterproof and breathable membranes have wide applications in various industries. For example, in outdoor sports, they are commonly used in outdoor clothing such as waterproof jackets and ski suits, as well as outdoor equipment like tents. In the medical field, they are mainly used in surgical gowns, bed sheets, and wound dressings. In the military, they are primarily used in combat uniforms and cold-weather clothing. In firefighting, they are mainly used for special protective gear. Currently, waterproof and breathable membranes are mainly used in outdoor clothing, and due to their special properties, market demand is continuously increasing.

[0003] In recent years, with the advancement of technology and the improvement of people's living standards, waterproof and breathable fabrics have developed rapidly and have been applied in many fields. Currently, the high-performance waterproof and breathable products on the market are mainly from the United States. The product line includes waterproof and breathable membranes and fabrics manufactured by the German company Sympatex. Gore-Tex is characterized by its lightness, thinness, and durability. It not only offers excellent waterproofness and breathability but also superior wind resistance, overcoming the common drawback of non-breathable waterproof membranes on the market. With several generations of development, Gore-Tex products have maintained their waterproofness and durability while continuously improving breathability, making them more comfortable to meet market and consumer demands. Currently... Besides being widely used in various outdoor sports, the product series is also used in military, security, and firefighting equipment. Sympatex is a hydrophilic non-porous membrane made from copolyether ester. By combining Sympatex film with different fabrics, composite structures with different uses can be obtained. Sympatex film has a high market share in Europe. This film is composed of 100% polyester and decomposes into nitrogen, hydrogen, and oxygen under natural conditions, making it environmentally friendly and recyclable. In addition, because it utilizes the macromolecular chains in the hydrophilic non-porous membrane for moisture conduction, its moisture permeability will not be affected by scratches or washing after a period of use. However, as people's functional requirements increase, its moisture permeability is gradually failing to meet people's needs. Summary of the Invention

[0004] The technical problem to be solved: The purpose of this invention is to provide a waterproof, breathable and moisture-permeable fabric, which is prepared by electrospinning nanofiber membranes using thermoplastic polyurethane and chitosan as raw materials, and then composited with the fabric to obtain a fabric that is waterproof, breathable and moisture-permeable at the same time.

[0005] Technical solution: A waterproof, breathable, and moisture-wicking fabric, the fabric comprising a TPU layer, a fabric layer, and a moisture-wicking and waterproof layer, wherein the TPU layer is a TPU electrospun film, the moisture-wicking and waterproof layer is a chitosan electrospun film, and the chitosan electrospun film contains nano-carbon balls / hydrotalcite sheet materials.

[0006] Preferably, the preparation method of the nanocarbon sphere / hydrotalcite sheet material includes the following steps:

[0007] S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution;

[0008] S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution;

[0009] S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always maintaining the pH of the mixed solution at 10-11. After the addition is complete, heat the reaction to obtain magnesium aluminum hydrotalcite.

[0010] S14. Add magnesium aluminum hydrotalcite to formamide, stir for 20-60 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite;

[0011] S15. The exfoliated magnesium aluminum hydrotalcite was added to a fructose aqueous solution, and then added to a hydrothermal reactor for heating and reaction to obtain nano-carbon spheres / hydrotalcite sheet materials;

[0012] S16. Add the nano-carbon spheres / hydrotalcite flakes to anhydrous ethanol, stir and disperse evenly, then add stearic acid, mix evenly to obtain a suspension, maintain the pH of the solution at 5.5, stir the reaction, and dry to obtain the modified nano-carbon spheres / hydrotalcite flakes. Preferably, the heating reaction temperature in step S13 is 70-90℃, and the time is 4-10h.

[0013] Preferably, in step S15, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution is 2-8 wt%, the concentration of the fructose aqueous solution is 0.2-0.6 mol / L, the hydrothermal reaction temperature is 170-185℃, and the hydrothermal reaction time is 8-20 h.

[0014] Preferably, in step S16, the mass ratio of the nanocarbon spheres / hydrotalcite sheet material to stearic acid is 5-8:1.

[0015] The above-mentioned method for preparing waterproof, breathable, and moisture-wicking fabric includes the following steps:

[0016] S1. Dissolve thermoplastic polyurethane in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 8-10%. Electrospin the TPU to obtain a TPU electrospun film.

[0017] S2. Soak the fabric in a 0.1-0.3wt% chitosan solution, stir and react, then dry. Adhere the TPU electrospun film to one side of the fabric layer by hot pressing. Then, coat the side of the TPU electrospun film that is not adhered with a layer of chitosan wet gel to obtain the fabric layer.

[0018] S3. Add nano-carbon balls / hydrotalcite flakes to the chitosan solution, stir and mix evenly, and use the side of the fabric layer containing the chitosan wet gel as the receiving surface. Prepare a moisture-wicking and waterproof layer on the outside of the fabric layer by electrospinning. Finally, freeze-dry to obtain a waterproof, breathable and moisture-wicking fabric.

[0019] Preferably, the porosity of the electrospun membrane in step S1 is 60-70%.

[0020] Preferably, the thickness of the chitosan hydrogel in step S2 is 0.1-0.2 mm.

[0021] Preferably, in step S3, the concentration of the nano-carbon spheres / hydrotalcite flakes in the chitosan solution is 5-8 wt%, the concentration of the chitosan solution is 0.8-1.2 wt%, and the porosity of the moisture-wicking and waterproof layer is 80-90%.

[0022] Preferably, in step S3, the freeze-drying temperature is -60 to -40°C, and the time is 10-20 hours.

[0023] Beneficial effects: The waterproof, breathable, and moisture-wicking fabric of this invention has the following advantages:

[0024] 1. This invention uses a hydrophobic TPU layer, a fabric layer, and a moisture-wicking and waterproof layer to form a composite fabric with directional moisture wicking. Before bonding the fabric with TPU, the fabric is first soaked in a low-concentration chitosan solution, allowing chitosan to permeate and load the pores of the fabric. The chitosan permeating the pores acts as a capillary. After the fabric is soaked in the low-concentration chitosan solution, a layer of wet chitosan gel is coated on the surface of the fabric. The wet chitosan gel can serve two functions. First, electrospinning can be performed directly on the surface of the chitosan gel. The composite of the electrospun film and the fabric does not require an adhesive, and the chitosan electrospun film can adhere well to the wet chitosan gel. Second, after the wet gel dries, its porous structure allows it to quickly evaporate the water adsorbed in the pores, improving the breathability and moisture permeability.

[0025] 2. In this invention, a nanofiber membrane is prepared by hydrothermal reaction of fructose in a fructose solution on a micro / nanosheet hydrotalcite. The fructose contains nano-carbon microspheres on the surface of the micro / nanosheet hydrotalcite. After hydrophobic modification, the prepared nano-carbon microsphere / hydrotalcite sheet material is added to a chitosan spinning solution. The prepared fiber membrane has a multi-level rough structure and low surface energy, achieving superhydrophobic properties. At the same time, the composite nanofiber membrane has a hydrophobic porous structure, which can prevent liquid water from permeating while transferring water vapor. Detailed Implementation

[0026] The present invention will be further described below with reference to embodiments. These embodiments are illustrative of the present invention, but the present invention is not limited to these embodiments:

[0027] Example 1

[0028] A method for preparing a waterproof, breathable, and moisture-wicking fabric, the method comprising the following steps:

[0029] S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a 10% TPU spinning solution. The TPU was then electrospun to obtain a TPU electrospun film with a porosity of 62.8%.

[0030] S2. Soak the fabric in a 0.1wt% chitosan solution, stir and react, then dry. Adhere the TPU electrospun film to one side of the fabric layer by hot pressing. Then, coat the side of the unbonded TPU electrospun film with a layer of chitosan wet gel with a thickness of 0.1mm to obtain the fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%.

[0031] S3. Add the nano-carbon ball / hydrotalcite sheet material to a chitosan solution with a concentration of 0.8wt%, and the concentration of the nano-carbon ball / hydrotalcite sheet material in the chitosan solution is 8wt%. After stirring and mixing evenly, take the side of the fabric layer containing the chitosan wet gel as the receiving surface, and prepare a moisture-wicking and waterproof layer with a porosity of 81.5% on the outside of the fabric layer by electrospinning. Finally, freeze-dry at a temperature of -60℃ for 20 hours to obtain a waterproof, breathable and moisture-wicking fabric.

[0032] The preparation method of the nanocarbon sphere / hydrotalcite sheet material includes the following steps:

[0033] S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution;

[0034] S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution;

[0035] S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always keeping the pH of the mixed solution at 10. After the addition is complete, heat the mixture at 70°C for 10 hours to obtain magnesium aluminum hydrotalcite.

[0036] S14. Add magnesium aluminum hydrotalcite to formamide, stir for 60 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite;

[0037] S15. The exfoliated magnesium aluminum hydrotalcite was added to a 0.2 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 2 wt%, and then added to a hydrothermal reactor for heating and reaction. The hydrothermal reaction temperature was 170℃ and the hydrothermal reaction time was 20 h to obtain nano-carbon spheres / hydrotalcite sheet materials.

[0038] S16. Add the nano-carbon spheres / hydrotalcite flakes to anhydrous ethanol, stir and disperse evenly, then add stearic acid. The mass ratio of nano-carbon spheres / hydrotalcite flakes to stearic acid is 5:1. Mix evenly to obtain a suspension. Keep the pH of the solution at 5.5, stir the reaction, and dry to obtain the modified nano-carbon spheres / hydrotalcite flakes.

[0039] Example 2

[0040] A method for preparing a waterproof, breathable, and moisture-wicking fabric, the method comprising the following steps:

[0041] S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 8%. The TPU was electrospun to obtain a TPU electrospun film with a porosity of 65.3%.

[0042] S2. Soak the fabric in a 0.3wt% chitosan solution, stir and react, then dry. Adhere the TPU electrospun film to one side of the fabric layer by hot pressing. Then, coat the side of the unbonded TPU electrospun film with a layer of chitosan wet gel with a thickness of 0.2mm to obtain the fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%.

[0043] S3. Add the nano-carbon ball / hydrotalcite sheet material to a chitosan solution with a concentration of 1.2wt%, and the concentration of the nano-carbon ball / hydrotalcite sheet material in the chitosan solution is 5wt%. After stirring and mixing evenly, take the side of the fabric layer containing the chitosan wet gel as the receiving surface, and prepare a moisture-wicking and waterproof layer with a porosity of 82.6% on the outside of the fabric layer by electrospinning. Finally, freeze-dry at a temperature of -40℃ for 1 hour to obtain a waterproof, breathable and moisture-wicking fabric.

[0044] The preparation method of the nanocarbon sphere / hydrotalcite sheet material includes the following steps:

[0045] S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution;

[0046] S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution;

[0047] S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always keeping the pH of the mixed solution at 11. After the addition is complete, heat the mixture at 90°C for 4 hours to obtain magnesium aluminum hydrotalcite.

[0048] S14. Add magnesium aluminum hydrotalcite to formamide, stir for 20 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite;

[0049] S15. The exfoliated magnesium aluminum hydrotalcite was added to a 0.6 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 8 wt%, and then added to a hydrothermal reactor for heating and reaction. The hydrothermal reaction temperature was 185℃ and the hydrothermal reaction time was 8 h to obtain nano-carbon spheres / hydrotalcite sheet materials.

[0050] S16. Add the nano-carbon spheres / hydrotalcite flakes to anhydrous ethanol, stir and disperse evenly, then add stearic acid. The mass ratio of nano-carbon spheres / hydrotalcite flakes to stearic acid is 8:1. Mix evenly to obtain a suspension. Keep the pH of the solution at 5.5, stir the reaction, and dry to obtain the modified nano-carbon spheres / hydrotalcite flakes.

[0051] Example 3

[0052] A method for preparing a waterproof, breathable, and moisture-wicking fabric, the method comprising the following steps:

[0053] S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 8.5%. The TPU was electrospun to obtain a TPU electrospun film with a porosity of 67%.

[0054] S2. Soak the fabric in a 0.15wt% chitosan solution, stir and react, then dry. Adhere the TPU electrospun film to one side of the fabric layer by hot pressing. Then, coat the side of the unbonded TPU electrospun film with a layer of chitosan wet gel with a thickness of 0.1mm to obtain the fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%.

[0055] S3. Add the nano-carbon ball / hydrotalcite sheet material to a 0.9wt% chitosan solution. The concentration of the nano-carbon ball / hydrotalcite sheet material in the chitosan solution is 7wt%. After stirring and mixing evenly, use the side of the fabric layer containing the chitosan wet gel as the receiving surface. Through electrospinning, a moisture-wicking and waterproof layer with a porosity of 85.5% is prepared on the outside of the fabric layer. Finally, freeze-dry the fabric at a temperature of -45℃ for 12 hours to obtain a waterproof, breathable, and moisture-wicking fabric.

[0056] The preparation method of the nanocarbon sphere / hydrotalcite sheet material includes the following steps:

[0057] S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution;

[0058] S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution;

[0059] S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always keeping the pH of the mixed solution at 10. After the addition is complete, heat the mixture at 75°C for 8 hours to obtain magnesium aluminum hydrotalcite.

[0060] S14. Add magnesium aluminum hydrotalcite to formamide, stir for 50 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite;

[0061] S15. The exfoliated magnesium aluminum hydrotalcite was added to a 0.5 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 4 wt%, and then added to a hydrothermal reactor for heating and reaction. The hydrothermal reaction temperature was 175℃ and the hydrothermal reaction time was 16 h to obtain nano-carbon spheres / hydrotalcite sheet materials.

[0062] S16. Add the nano-carbon spheres / hydrotalcite flakes to anhydrous ethanol, stir and disperse evenly, then add stearic acid. The mass ratio of nano-carbon spheres / hydrotalcite flakes to stearic acid is 6:1. Mix evenly to obtain a suspension. Keep the pH of the solution at 5.5, stir the reaction, and dry to obtain the modified nano-carbon spheres / hydrotalcite flakes.

[0063] Example 4

[0064] A method for preparing a waterproof, breathable, and moisture-wicking fabric, the method comprising the following steps:

[0065] S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 9.5%. The TPU was electrospun to obtain a TPU electrospun film with a porosity of 62%.

[0066] S2. Soak the fabric in a 0.25wt% chitosan solution, stir and react, then dry. Adhere the TPU electrospun film to one side of the fabric layer by hot pressing. Then, coat the side of the unbonded TPU electrospun film with a layer of chitosan wet gel with a thickness of 0.2mm to obtain the fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%.

[0067] S3. Add the nano-carbon ball / hydrotalcite sheet material to a chitosan solution with a concentration of 1.1 wt%. The concentration of the nano-carbon ball / hydrotalcite sheet material in the chitosan solution is 6 wt%. After stirring and mixing evenly, take the side of the fabric layer containing the chitosan wet gel as the receiving surface, and prepare a moisture-wicking and waterproof layer with a porosity of 86.1% on the outside of the fabric layer by electrospinning. Finally, freeze-dry the fabric at a temperature of -55℃ for 18 hours to obtain a waterproof, breathable and moisture-wicking fabric.

[0068] The preparation method of the nanocarbon sphere / hydrotalcite sheet material includes the following steps:

[0069] S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution;

[0070] S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution;

[0071] S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always keeping the pH of the mixed solution at 11. After the addition is complete, heat the mixture at 85°C for 6 hours to obtain magnesium aluminum hydrotalcite.

[0072] S14. Add magnesium aluminum hydrotalcite to formamide, stir for 30 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite;

[0073] S15. The exfoliated magnesium aluminum hydrotalcite was added to a 0.3 mol / L fructose aqueous solution, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution was 6 wt%, and then added to a hydrothermal reactor for heating and reaction. The hydrothermal reaction temperature was 180℃ and the hydrothermal reaction time was 12 h to obtain nano-carbon spheres / hydrotalcite sheet materials.

[0074] S16. Add the nano-carbon spheres / hydrotalcite flakes to anhydrous ethanol, stir and disperse evenly, then add stearic acid, the mass ratio of nano-carbon spheres / hydrotalcite flakes to stearic acid is 7:1, mix evenly to obtain a suspension, keep the pH of the solution at 5.5, stir the reaction, and dry to obtain the modified nano-carbon spheres / hydrotalcite flakes.

[0075] Example 5

[0076] A method for preparing a waterproof, breathable, and moisture-wicking fabric, the method comprising the following steps:

[0077] S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a 9% TPU spinning solution. The TPU was then electrospun to obtain a TPU electrospun film with a porosity of 66.2%.

[0078] S2. Soak the fabric in a 0.2wt% chitosan solution, stir and react, then dry. Adhere the TPU electrospun film to one side of the fabric layer by hot pressing. Then, coat the side of the unbonded TPU electrospun film with a layer of chitosan wet gel with a thickness of 0.13mm to obtain the fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%.

[0079] S3. Add the nano-carbon ball / hydrotalcite sheet material to a 1wt% chitosan solution. The concentration of the nano-carbon ball / hydrotalcite sheet material in the chitosan solution is 6.5wt%. After stirring and mixing evenly, use the side of the fabric layer containing the chitosan wet gel as the receiving surface. Through electrospinning, a moisture-wicking and waterproof layer with a porosity of 88.2% is prepared on the outside of the fabric layer. Finally, freeze-dry the fabric at -50℃ for 15 hours to obtain a waterproof, breathable and moisture-wicking fabric.

[0080] The preparation method of the nanocarbon sphere / hydrotalcite sheet material includes the following steps:

[0081] S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution;

[0082] S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution;

[0083] S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always keeping the pH of the mixed solution at 11. After the addition is complete, heat the mixture at 80°C for 7 hours to obtain magnesium aluminum hydrotalcite.

[0084] S14. Add magnesium aluminum hydrotalcite to formamide, stir for 40 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite;

[0085] S15. The exfoliated magnesium aluminum hydrotalcite was added to a 0.45 mol / L fructose aqueous solution with a concentration of 5 wt%. The solution was then added to a hydrothermal reactor and heated for 15 h to obtain nano-carbon spheres / hydrotalcite sheet materials.

[0086] S16. Add the nano-carbon spheres / hydrotalcite flakes to anhydrous ethanol, stir and disperse evenly, then add stearic acid. The mass ratio of nano-carbon spheres / hydrotalcite flakes to stearic acid is 6.5:1. Mix evenly to obtain a suspension. Keep the pH of the solution at 5.5, stir the reaction, and dry to obtain the modified nano-carbon spheres / hydrotalcite flakes.

[0087] Comparative Example 1

[0088] A method for preparing a waterproof, breathable, and moisture-wicking fabric, the method comprising the following steps:

[0089] S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a 9% TPU spinning solution. The TPU was then electrospun to obtain a TPU electrospun film with a porosity of 63.5%.

[0090] S2. Soak the fabric in a 0.2wt% chitosan solution, stir and react, then dry. Adhere the TPU electrospun film to one side of the fabric layer by hot pressing. Then, coat the side of the unbonded TPU electrospun film with a layer of chitosan wet gel with a thickness of 0.13mm to obtain the fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%.

[0091] S3. Modified hydrotalcite flakes were added to a 1 wt% chitosan solution, and the concentration of the modified hydrotalcite flakes in the chitosan solution was 6.5 wt%. After stirring and mixing evenly, the side of the fabric layer containing the chitosan wet gel was used as the receiving surface. A moisture-wicking and waterproof layer with a porosity of 86.3% was prepared on the outside of the fabric layer by electrospinning. Finally, the fabric was freeze-dried at -50℃ for 15 hours to obtain a waterproof, breathable and moisture-wicking fabric.

[0092] The method for preparing the modified hydrotalcite sheet material includes the following steps:

[0093] S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution;

[0094] S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution;

[0095] S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always keeping the pH of the mixed solution at 11. After the addition is complete, heat the mixture at 80°C for 7 hours to obtain magnesium aluminum hydrotalcite.

[0096] S14. Add magnesium aluminum hydrotalcite to formamide, stir for 40 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite;

[0097] S15. Add the stripped magnesium aluminum hydrotalcite to anhydrous ethanol, stir and disperse evenly, then add stearic acid. The mass ratio of the stripped magnesium aluminum hydrotalcite to stearic acid is 6.5:1. Mix evenly to obtain a suspension. Keep the pH of the solution at 5.5, stir to react, and dry to obtain modified hydrotalcite sheet material.

[0098] Comparative Example 2

[0099] A method for preparing a waterproof, breathable, and moisture-wicking fabric, the method comprising the following steps:

[0100] S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a 9% TPU spinning solution. The TPU was then electrospun to obtain a TPU electrospun film with a porosity of 65.5%.

[0101] S2. Soak the fabric in a 0.2wt% chitosan solution, stir and react, then dry. Adhere the TPU electrospun film to one side of the fabric layer by hot pressing. Then, coat the side of the unbonded TPU electrospun film with a layer of chitosan wet gel with a thickness of 0.13mm to obtain the fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%.

[0102] S3. Add the nano-carbon ball / hydrotalcite sheet material to a 1 wt% chitosan solution. The concentration of the nano-carbon ball / hydrotalcite sheet material in the chitosan solution is 6.5 wt%. After stirring and mixing evenly, use the side of the fabric layer containing the chitosan wet gel as the receiving surface. Through electrospinning, a moisture-wicking and waterproof layer with a porosity of 86.5% is prepared on the outside of the fabric layer. Finally, freeze-dry the fabric at -50℃ for 15 hours to obtain a waterproof, breathable and moisture-wicking fabric.

[0103] The preparation method of the nanocarbon sphere / hydrotalcite sheet material includes the following steps:

[0104] S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution;

[0105] S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution;

[0106] S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always keeping the pH of the mixed solution at 11. After the addition is complete, heat the mixture at 80°C for 7 hours to obtain magnesium aluminum hydrotalcite.

[0107] S14. Add magnesium aluminum hydrotalcite to formamide, stir for 40 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite;

[0108] S15. The exfoliated magnesium aluminum hydrotalcite was added to a 0.45 mol / L fructose aqueous solution, with the magnesium aluminum hydrotalcite concentration in the fructose aqueous solution being 5 wt%. Then, it was added to a hydrothermal reactor and heated for reaction at a hydrothermal reaction temperature of 180℃ for 15 h to obtain nano-carbon spheres / hydrotalcite sheet materials.

[0109] Comparative Example 3

[0110] A method for preparing a waterproof, breathable, and moisture-wicking fabric, the method comprising the following steps:

[0111] S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a 9% TPU spinning solution. The TPU was then electrospun to obtain a TPU electrospun film with a porosity of 64.5%.

[0112] S2. The TPU electrospun film is bonded to one side of the fabric layer by hot pressing. Then, a layer of chitosan wet gel with a thickness of 0.13 mm is coated on the side of the unbonded TPU electrospun film to obtain the fabric layer, wherein the mass fraction of chitosan wet gel is 2 wt%.

[0113] S3. Add the nano-carbon ball / hydrotalcite sheet material to a 1 wt% chitosan solution. The concentration of the nano-carbon ball / hydrotalcite sheet material in the chitosan solution is 6.5 wt%. After stirring and mixing evenly, use the side of the fabric layer containing the chitosan wet gel as the receiving surface. Through electrospinning, a moisture-wicking and waterproof layer with a porosity of 85.9% is prepared on the outside of the fabric layer. Finally, freeze-dry the fabric at a temperature of -50℃ for 15 hours to obtain a waterproof, breathable, and moisture-wicking fabric.

[0114] The preparation method of the nanocarbon sphere / hydrotalcite sheet material includes the following steps:

[0115] S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution;

[0116] S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution;

[0117] S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always keeping the pH of the mixed solution at 11. After the addition is complete, heat the mixture at 80°C for 7 hours to obtain magnesium aluminum hydrotalcite.

[0118] S14. Add magnesium aluminum hydrotalcite to formamide, stir for 40 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite;

[0119] S15. The exfoliated magnesium aluminum hydrotalcite was added to a 0.45 mol / L fructose aqueous solution with a concentration of 5 wt%. The solution was then added to a hydrothermal reactor and heated for 15 h to obtain nano-carbon spheres / hydrotalcite sheet materials.

[0120] S16. Add the nano-carbon spheres / hydrotalcite flakes to anhydrous ethanol, stir and disperse evenly, then add stearic acid. The mass ratio of nano-carbon spheres / hydrotalcite flakes to stearic acid is 6.5:1. Mix evenly to obtain a suspension. Keep the pH of the solution at 5.5, stir the reaction, and dry to obtain the modified nano-carbon spheres / hydrotalcite flakes.

[0121] Comparative Example 4

[0122] A method for preparing a waterproof, breathable, and moisture-wicking fabric, the method comprising the following steps:

[0123] S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a 9% TPU spinning solution. The TPU was then electrospun to obtain a TPU electrospun film with a porosity of 61.5%.

[0124] S2. Soak the fabric in a 0.2wt% chitosan solution, stir and react, then dry. Adhere the TPU electrospun film to one side of the fabric layer by hot pressing to obtain the fabric layer.

[0125] S3. Add the nano-carbon ball / hydrotalcite sheet material to a 1wt% chitosan solution. The concentration of the nano-carbon ball / hydrotalcite sheet material in the chitosan solution is 6.5wt%. After stirring and mixing evenly, use the unbonded side of the fabric layer as the receiving surface. Prepare a moisture-wicking and waterproof layer with a porosity of 86.2% on the outside of the fabric layer by electrospinning. Finally, freeze-dry at -50℃ for 15 hours to obtain a waterproof, breathable and moisture-wicking fabric.

[0126] The preparation method of the nanocarbon sphere / hydrotalcite sheet material includes the following steps:

[0127] S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution;

[0128] S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution;

[0129] S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always keeping the pH of the mixed solution at 11. After the addition is complete, heat the mixture at 80°C for 7 hours to obtain magnesium aluminum hydrotalcite.

[0130] S14. Add magnesium aluminum hydrotalcite to formamide, stir for 40 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite;

[0131] S15. The exfoliated magnesium aluminum hydrotalcite was added to a 0.45 mol / L fructose aqueous solution with a concentration of 5 wt%. The solution was then added to a hydrothermal reactor and heated for 15 h to obtain nano-carbon spheres / hydrotalcite sheet materials.

[0132] S16. Add the nano-carbon spheres / hydrotalcite flakes to anhydrous ethanol, stir and disperse evenly, then add stearic acid. The mass ratio of nano-carbon spheres / hydrotalcite flakes to stearic acid is 6.5:1. Mix evenly to obtain a suspension. Keep the pH of the solution at 5.5, stir the reaction, and dry to obtain the modified nano-carbon spheres / hydrotalcite flakes.

[0133] Comparative Example 5

[0134] A method for preparing a waterproof, breathable, and moisture-wicking fabric, the method comprising the following steps:

[0135] S1. Thermoplastic polyurethane was dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a 9% TPU spinning solution. The TPU was then electrospun to obtain a TPU electrospun film with a porosity of 67.5%.

[0136] S2. Soak the fabric in a 1wt% chitosan solution, stir and react, then dry. Adhere the TPU electrospun film to one side of the fabric layer by hot pressing. Then, coat the side of the unbonded TPU electrospun film with a layer of chitosan wet gel with a thickness of 0.13mm to obtain the fabric layer, wherein the mass fraction of the chitosan wet gel is 2wt%.

[0137] S3. Add the nano-carbon ball / hydrotalcite sheet material to a 1wt% chitosan solution. The concentration of the nano-carbon ball / hydrotalcite sheet material in the chitosan solution is 6.5wt%. After stirring and mixing evenly, use the side of the fabric layer containing the chitosan wet gel as the receiving surface. Through electrospinning, a moisture-wicking and waterproof layer with a porosity of 86.1% is prepared on the outside of the fabric layer. Finally, freeze-dry the fabric at a temperature of -50℃ for 15 hours to obtain a waterproof, breathable, and moisture-wicking fabric.

[0138] The preparation method of the nanocarbon sphere / hydrotalcite sheet material includes the following steps:

[0139] S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution;

[0140] S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution;

[0141] S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always keeping the pH of the mixed solution at 11. After the addition is complete, heat the mixture at 80°C for 7 hours to obtain magnesium aluminum hydrotalcite.

[0142] S14. Add magnesium aluminum hydrotalcite to formamide, stir for 40 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite;

[0143] S15. The exfoliated magnesium aluminum hydrotalcite was added to a 0.45 mol / L fructose aqueous solution with a concentration of 5 wt%. The solution was then added to a hydrothermal reactor and heated for 15 h to obtain nano-carbon spheres / hydrotalcite sheet materials.

[0144] S16. Add the nano-carbon spheres / hydrotalcite flakes to anhydrous ethanol, stir and disperse evenly, then add stearic acid. The mass ratio of nano-carbon spheres / hydrotalcite flakes to stearic acid is 6.5:1. Mix evenly to obtain a suspension. Keep the pH of the solution at 5.5, stir the reaction, and dry to obtain the modified nano-carbon spheres / hydrotalcite flakes.

[0145] Performance tests of the fabrics prepared in Examples 1-5 and Comparative Examples 1-5:

[0146] In the above examples and comparative examples, the fabric layer was made of 230T polyester taffeta. The hydrostatic pressure was tested according to GB / T 4744-2013 "Test and Evaluation of Waterproof Performance of Textiles - Hydrostatic Pressure Method". The moisture permeability was mainly tested by the evaporation method, namely GB / T 12704.2-2009 "Textiles - Test Methods for Moisture Permeability of Fabrics - Part 2: Evaporation Method".

[0147] Table 1 shows the water resistance and moisture permeability values ​​of the fabric before washing.

[0148]

[0149]

[0150] According to GB / T 32614-2016 "Outdoor Sports Apparel - Waterproof Jackets", the functional requirements for Class I waterproof jacket fabrics are: moisture permeability ≥ 5000g / (m²) before washing. 2 • 24h), hydrostatic pressure ≥50kPa, the above examples and comparative examples can all achieve the Class I function of the windbreaker fabric.

[0151] Table 2 shows the water resistance and moisture permeability values ​​of the fabric after washing.

[0152] Example 1 126 12154 Example 2 122 12899 Example 3 120 12569 Example 4 120 12871 Example 5 123 13001 Comparative Example 1 78 12956 Comparative Example 2 45 12873 Comparative Example 3 119 11063 Comparative Example 4 125 8865 Comparative Example 5 122 7812

[0153] Washed three times according to washing procedure 5A of GB / T 8629-2001 "Home Washing and Drying Procedures for Textile Testing". The water-repellent properties were slightly affected after washing, but the moisture-permeable properties were good.

[0154] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a waterproof, breathable, and moisture-permeable fabric, characterized in that: The preparation method includes the following steps: S1. Thermoplastic polyurethane is dissolved in a mixed solution of N,N-dimethylformamide and tetrahydrofuran in a volume ratio of 1:1 to prepare a TPU spinning solution with a concentration of 8-10%. The TPU is then electrospun to obtain a TPU electrospun film. S2. Soak the fabric in a 0.1-0.3wt% chitosan solution, stir and react, then dry. Adhere the TPU electrospun film to one side of the fabric layer by hot pressing. Then, coat the side without the TPU electrospun film with a layer of chitosan wet gel to obtain the fabric layer. S3. Add the modified carbon nanospheres / hydrotalcite flakes to the chitosan solution, stir and mix evenly, and use the side of the fabric layer containing the chitosan wet gel as the receiving surface. Prepare a moisture-wicking and waterproof layer on the outside of the fabric layer by electrospinning. Finally, freeze-dry to obtain a waterproof, breathable and moisture-wicking fabric. The preparation method of the modified carbon nanospheres / hydrotalcite sheet material includes the following steps: S11. Add magnesium nitrate hexahydrate and aluminum nitrate nonahydrate to deionized water in a molar ratio of 3:1, stir to dissolve, and obtain a mixed salt solution; S12. Add sodium hydroxide and sodium carbonate to deionized water in a molar ratio of 1:1, stir to dissolve, and obtain a mixed alkaline solution; S13. Add the mixed salt solution and the mixed alkali solution dropwise into the container at the same rate, stirring and reacting simultaneously, always maintaining the pH of the mixed solution at 10-11. After the addition is complete, heat the reaction to obtain magnesium aluminum hydrotalcite. S14. Add magnesium aluminum hydrotalcite to formamide, stir for 20-60 h, centrifuge to collect the supernatant, wash and dry to obtain the exfoliated magnesium aluminum hydrotalcite; S15. The exfoliated magnesium aluminum hydrotalcite was added to a fructose aqueous solution, and then added to a hydrothermal reactor for heating and reaction to obtain nano-carbon spheres / hydrotalcite sheet materials; S16. Add the nano-carbon spheres / hydrotalcite flakes to anhydrous ethanol, stir and disperse evenly, then add stearic acid, mix evenly to obtain a suspension, keep the pH of the solution at 5.5, stir the reaction, and dry to obtain the modified nano-carbon spheres / hydrotalcite flakes.

2. The method for preparing the waterproof, breathable, and moisture-permeable fabric according to claim 1, characterized in that: In step S13, the heating reaction temperature is 70-90℃ and the time is 4-10h.

3. The method for preparing the waterproof, breathable, and moisture-permeable fabric according to claim 1, characterized in that: In step S15, the concentration of magnesium aluminum hydrotalcite in the fructose aqueous solution is 2-8 wt%, the concentration of the fructose aqueous solution is 0.2-0.6 mol / L, the hydrothermal reaction temperature is 170-185℃, and the hydrothermal reaction time is 8-20 h.

4. The method for preparing the waterproof, breathable, and moisture-permeable fabric according to claim 1, characterized in that: In step S16, the mass ratio of nanocarbon spheres / hydrotalcite flakes to stearic acid is 5-8:

1.

5. The method for preparing the waterproof, breathable, and moisture-permeable fabric according to claim 1, characterized in that: In step S1, the porosity of the electrospun membrane is 60-70%.

6. The method for preparing the waterproof, breathable, and moisture-permeable fabric according to claim 1, characterized in that: The thickness of the chitosan hydrogel in step S2 is 0.1-0.2 mm.

7. The method for preparing the waterproof, breathable, and moisture-permeable fabric according to claim 1, characterized in that: In step S3, the concentration of the nano-carbon spheres / hydrotalcite flakes in the chitosan solution is 5-8 wt%, the concentration of the chitosan solution is 0.8-1.2 wt%, and the porosity of the moisture-wicking and waterproof layer is 80-90%.

8. The method for preparing the waterproof, breathable, and moisture-permeable fabric according to claim 1, characterized in that: In step S3, the freeze-drying temperature is -60~-40℃ and the time is 10-20h.

9. The waterproof, breathable, and moisture-permeable fabric prepared by the method according to claim 1, characterized in that: The fabric includes a TPU layer, a fabric layer, and a moisture-wicking and waterproof layer. The TPU layer is a TPU electrospun film, and the moisture-wicking and waterproof layer is a chitosan electrospun film. The chitosan electrospun film contains modified nano-carbon balls / hydrotalcite sheet materials.

Citation Information

Patent Citations

  • Waterproof electrostatic spinning membrane with high moisture permeability and air permeability as well as preparation method and application thereof

    CN117468172A

  • Breathable and moisture-permeable composite TPU material and preparation method thereof

    CN117779351A